Analisis Penjadwalan Proyek Boiler Dengan Metode Cpm (Critical Path Method) Dan Pert (Program Evaluation And Review Technique) - Zainul Aziz, Labib; Dwito Armono , Haryo (Fakultas Ekonomi Universitas Gresik, 2023)
Before the project runs, initial planning is carried out including schedule planning. The 35 Ton / Hour Boiler Project for 3 Units is a project owned by PT Supreme Paper Solution and appoints CV INTAN WELL as a contractor with a duration of 90 days and a contract value of 4.3 billion. The number of activities and resources required in completing this boiler project so that an optimal scheduling analysis is needed so that there is no project delay so that the contractor does not get a penalty fee and does not have an impact on company production.This research will form a network diagram and WBS, analyse work scheduling with the CPM and PERT methods for reference to systematic and effective installation implementation based on the network diagram that has been made, comparison of project implementation duration between the CPM and PERT methods and form an S-Curve of the selected duration. The results of this schedule planning can be a reference recommendation for project implementation in the field.The results of this study using the CPM method. The Boiler Installation Project can be completed within 90 days. And the critical path lies in activity codes A1, B1, B2, B3, B7, B9, B10, I1, I2, J1. These activities are equipment preparation, Manpower and Safety Person (A1), Support Chain Grate H Beam 150 & Plate 70X70 (B1), Frame Chain Grate & Install Part Chain Grate (B2), Install Boiler Header (Right, Left, Rear Lateral, Middle Lateral) (B3), Install Water Wall Diameter 51mm and Fit Up / Welding Evaporator (B7), Penetrant Test 100% Pipe to Header, Pipe to Drum (B9), X-Ray Water Wall pipe (B10), Flushing & Hydrotest Boiler (I1), Commissioning Test (I2) and Ijin Depnaker (J1). Whereas with the PERTP method the Boiler Installation Project can be completed within a period of 105 days. In this method, duration variant sampling is carried out with probability results for a duration of 90 days = 0.2%, 95 days = 1%, 100 days probability = 12%, 105 days = 50%, 110 days = 88% and 115 days = 99%. In the calculation, it is also found that the critical trajectory in the PERT method is the same as the critical trajectory with the CPM method. This project must be closely monitored, especially critical activities because the s-curve graph rises significantly. So that the planned project duration can be carried out on time.